2013
DOI: 10.4161/trns.23772
|View full text |Cite
|
Sign up to set email alerts
|

Of mice and men

Abstract: T he clinical importance of tumor suppressor p53 makes it one of the most studied transcription factors. A comparison of mammalian p53 transcriptional repertoires may help identify fundamental principles in genome evolution and better understand cancer processes. Here we summarize mechanisms underlying the divergence of mammalian p53 transcriptional repertoires, with an emphasis on the rapid evolution of fuzzy tandem repeats containing p53 response elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…This number is even smaller when also mouse- and human-specific genome regions are considered. For example, it was reported that p53REs can be shaped by long terminal repeats from endogenous retroviruses ( 34 , 35 ), long interspersed nuclear repeats (LINEs; ( 37 )), and ALU repeats ( 36 , 38 ) in humans and fuzzy tandem repeats in mice ( 163 , 241 ). It was shown that p53 oscillates faster in mouse and rat cells than in cells from human, monkey, or dog.…”
Section: Evolution Of the P53 Gene Regulatory Network In Vertebratesmentioning
confidence: 99%
“…This number is even smaller when also mouse- and human-specific genome regions are considered. For example, it was reported that p53REs can be shaped by long terminal repeats from endogenous retroviruses ( 34 , 35 ), long interspersed nuclear repeats (LINEs; ( 37 )), and ALU repeats ( 36 , 38 ) in humans and fuzzy tandem repeats in mice ( 163 , 241 ). It was shown that p53 oscillates faster in mouse and rat cells than in cells from human, monkey, or dog.…”
Section: Evolution Of the P53 Gene Regulatory Network In Vertebratesmentioning
confidence: 99%